2016
DOI: 10.1016/j.gie.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Another modality to treat esophageal cancer?

Abstract: Minimally invasive endoscopic therapy has come of age in the last decade. We now treat dysplastic Barrett's esophagus very effectively with endoscopic resection and radiofrequency ablation. Endoscopic submucosal dissection is increasingly used for early squamous cancers and also for spreading dysplasia within the esophagus. For locally advanced disease in both squamous and adenocarcinomas, chemoradiotherapy followed by surgery has, in the last few years, become a standard therapy [1]. But how do we help people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…5,6 Besides the basic function of the sent, a series of anticancer drug-loaded stents such as paclitaxel or 5-fluorouracil/ esophageal stent combination have been prepared by covering a nitinol stent with a bilayer polymer shell. 7,8 These drugloaded stents exhibited a prolonged and sustained unidirectional cancer drug release behavior. 9,10 In vivo experiments showed that the concentration of drug in the stent-contacted tissues was significantly higher than the other organs, for example, the heart, spleen, liver, kidneys, lung, and blood.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Besides the basic function of the sent, a series of anticancer drug-loaded stents such as paclitaxel or 5-fluorouracil/ esophageal stent combination have been prepared by covering a nitinol stent with a bilayer polymer shell. 7,8 These drugloaded stents exhibited a prolonged and sustained unidirectional cancer drug release behavior. 9,10 In vivo experiments showed that the concentration of drug in the stent-contacted tissues was significantly higher than the other organs, for example, the heart, spleen, liver, kidneys, lung, and blood.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In clinical medicine, a stent is a plastic or metal tube inserted into a duct or the lumen of an anatomic vessel to keep the passageway open. , Diverse stents are widely used for different purposes; for example, vascular and biliary stents expand coronary arteries and allow the flow of urine between the bladder and kidneys, respectively. , Esophageal stents are used for the palliative treatment of advanced esophageal cancer. , Besides the basic function of the sent, a series of anticancer drug-loaded stents such as paclitaxel or 5-fluorouracil/esophageal stent combination have been prepared by covering a nitinol stent with a bilayer polymer shell. , These drug-loaded stents exhibited a prolonged and sustained unidirectional cancer drug release behavior. , In vivo experiments showed that the concentration of drug in the stent-contacted tissues was significantly higher than the other organs, for example, the heart, spleen, liver, kidneys, lung, and blood. , Therefore, drug-loaded stents can be used for localized release of drugs and tumor chemotherapy. This is a highly nontoxic and efficient potential treatment modality for patients with esophageal cancer. However, anticancer drugs kill cancer cells as well as normal cells at the same time, thus usually causing some unpleasant side effects …”
Section: Introductionmentioning
confidence: 99%